A Mixed-Method Study on the Assessment of Factors Influencing Nurses' Provision of Spiritual Care - Fradelos, Evangelos C.; Alikari, Victoria; Artemi, Sofia; Missouridou, Evdokia; Mangoulia, Polyxeni; Kyranou, Maria; Saridi, Maria; Toska, Aikaterini; Tsaras, Konstantinos; Tzavella, Foteini (My University, 2024)
The purpose of this study was to explore factors that influence nurses’ beliefs about offering spiritual care. Study Design: A mixed-method study design, incorporating both quantitative (questionnaire) and qualitative research, was used for this study (focus group discussion). Methods: The questionnaires were completed by a convenience sample of nurses and their assistants working in two public hospitals. These questionnaires included the Greek versions of the FACIT-Sp-12, SCIPS, NEO-FFI, and the Spiritual Climate Scale, as well as a specially designed questionnaire to gather demographic, socioeconomic, and professional information about the study population (SCS). Three nurses and two nursing assistants who worked in public hospitals and were chosen through purposive sampling made up the sample for the qualitative study. In utilizing inductive content analysis methodology, a qualitative analysis was carried out. Results: Greek nurses frequently offer spiritual care to their patients, primarily existential spiritual care. It was discovered that the spiritual climate, the nurses’ positive coherence, and their educational level all exert a favorable effect on total spiritual care. Three categories and seven subcategories were used to describe the participants’ prior experiences with spiritual care. Conclusions: Greek nurses frequently offer spiritual care to their patients, and both internal and external factors influence their attitudes in this regard.
Keywords: spirituality; nurses; spiritual care